(untitled) (Comprehensive Journal of Science, 2025)
This research undertakes an in-depth study of the Statement of the Companion (Qawl al-Sahabi), examining its conceptual definition, scholarly status, and the extent of its authoritativeness (Hujjiyyah) within Usuli (juristic-methodological) inference. The Companions are revered as the best generation, the bearers of the Shari’ah (Islamic Law), and the trustees of the Divine Revelation, chosen by God to accompany the Prophet (peace be upon him) and convey his message. The study’s significance stems from its focus on Qawl al-Sahabi, a source of evidence subject to considerable debate among scholars of Usul al-Fiqh (Principles of Jurisprudence). The central problem is to precisely locate Qawl al-Sahabi within the hierarchy of Islamic legislative sources and determine its binding force. While scholars agree it is not an independent source of legislation, its authoritativeness is contentious when no explicit text exists in the primary sources (the Qur’an and Sunnah). A subsidiary issue explores the reliance on the statements and juristic rulings (Ijtihadat) of the Rightly Guided Caliphs (al-Khulafa’ al-Rashidun), in light of prophetic texts commanding adherence to The research addresses the following questions: What constitutes the Companion’s statement? What is its standing in Usuli inference? What is the scope of its authoritativeness? Is it a binding proof in the absence of a legal text? What are the controlling principles (Ḍawābiṭ) that govern its evidential use? The objectives are to provide a sound Usuli foundation for the issue, clarify its concept, systematically review the different scholarly schools of thought regarding its authoritativeness, analyze and critique their respective evidence, and ultimately propose a controlled, scholarly preference that clearly delineates the boundaries for using the Companion’s statement in legal inference. The methodology employed is inductive and analytical, involving a comprehensive survey of scholars’ opinions, followed by rigorous analysis and discussion. The research is structured into two main sections: the first defines the Companion and details his virtue in the Qur’an and Sunnah, and the second explores the schools of thought concerning the Companion’s statement and its authoritativeness. The study concludes with several key findings, notably that the Companion holds a distinguished scholarly and legal status, and his statement functions as a strong legal indicator (Qarīnah) in legal inference. It is deemed authoritative, subject to specific, recognized conditions and controlling principles, by a significant group of scholars, especially when it does not contradict an explicit text or a consensus (Ijmāʿ), and when no opposing view from another Companion is known. The most important recommendation is the necessity for an in-depth Usuli study of all disputed sources of evidence, alongside highlighting the methodological approach of the Salaf (Pious Predecessors) in utilizing the Companions’ statements. This effort is crucial for rationalizing the process of contemporary Ijtihad (independent legal reasoning) and ensuring its connection to the established principles of legal inference.